2008
DOI: 10.1177/1420326x08089251
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bioaerosol Concentrations in Different Indoor Environments

Abstract: The aim of this study was the assessment of bioaerosols in different indoor environments. The study was performed using volumetric culture plate air sampling to determine the concentration of viable bioaerosols. The results revealed that 60.9% of air samples from public places and all air samples collected in food processing plants had unacceptable levels of micro-organisms. This was based on a suggested standard which proposes that concentrations of viable micro-organisms should be no higher than 300 CFU · m-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…inhibition in the air samples caused by other species because of different growth rates [35,36]. We also observed that pig farms, poultry farms and WWTP presented significant differences in terms of the number of species isolated in the air and in the surface samples, in comparison with cork industries.…”
Section: Discussionsupporting
confidence: 48%
“…inhibition in the air samples caused by other species because of different growth rates [35,36]. We also observed that pig farms, poultry farms and WWTP presented significant differences in terms of the number of species isolated in the air and in the surface samples, in comparison with cork industries.…”
Section: Discussionsupporting
confidence: 48%
“…Similarly, the most commonly reported fungal species in indoor environments are Alternaria, Aspergillus, Cladosporium, and Penicillium (Zorman and Jeršek 2008;Bernasconi et al, 2010). Exposure to indoor fungi such as Alternaria, Aspergillus, and Penicillium can exacerbate symptoms of asthma and allergic rhinitis in susceptible individuals (Portnoy et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Fungi -Fungal strains which are proportionally of importance in indoor air samples are comprised of the genera Alternaria, Aspergillus, Cladosporium, and Penicillium [121][122][123][124][125][126]. All fungal strains are able to form spores which are resistant to changing environmental conditions.…”
Section: Composition Of Bioaerosolsmentioning
confidence: 99%